Partisipasi Pengguna dan Dukungan Manajemen Puncak terhadap Kepuasan Pengguna Sistem Informasi Akuntansi dengan Kompleksitas Tugas sebagai Variabel Moderasi - Erniwati, Erniwati; EDT, Risa Wahyuni; Amar, Syamsul; Syahrizal, Syahrizal (Universitas Batanghari Jambi, 2025)
This study aims to examine the effect of user participation and top management support on user satisfaction of accounting information systems (AIS), with task complexity as a moderating variable. The research subjects were supermarket employees in Padang Pariaman Regency who use AIS in their daily operations. A quantitative approach was applied using Partial Least Square (PLS) with 30 respondents. The findings indicate that user participation has a positive and significant effect on user satisfaction, while top management support has a positive but insignificant effect. Furthermore, task complexity does not moderate the relationship between user participation or top management support and user satisfaction. These results suggest that user satisfaction is more strongly influenced by direct employee involvement in system utilization rather than structural support from management or the complexity of tasks. This study highlights the importance of individual factors in determining AIS success in the retail sector.